2019
DOI: 10.1002/cpdd.704
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo‐Controlled Trial to Assess the Effects of 8 Weeks of Administration of GSK256073, a Selective GPR109A Agonist, on High‐Density Lipoprotein Cholesterol in Subjects With Dyslipidemia

Abstract: GPR109A (HM74A), a G‐protein‐coupled receptor, is hypothesized to mediate lipid and lipoprotein changes and dermal flushing associated with niacin administration. GSK256073 (8‐chloro‐3‐pentyl‐1H‐purine‐2,6[3H,7H]‐dione) is a selective GPR109A agonist shown to suppress fatty acid levels and produce mild flushing in short‐term clinical studies. This study evaluated the effects of GSK256073 on lipids in subjects with low high‐density lipoprotein cholesterol (HDLc). Subjects (n = 80) were randomized (1:1:1:1) to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…lowered circulating free fatty acids, they did not deliver the expected niacin-like effects on circulating lipoproteins in patients 4 . Subsequently, this lack of effect on lipoprotein levels was also reported for GSK256073 37 . Thus, although this eliminated HCAR2/GPR109A as a drug target for the treatment of dyslipidemia, HCAR2 agonists do inhibit lipolysis, which potentially could be beneficial in e.g.…”
Section: Hcar2 As a Drug Target – From Dyslipidemia And Diabetes To I...mentioning
confidence: 72%
“…lowered circulating free fatty acids, they did not deliver the expected niacin-like effects on circulating lipoproteins in patients 4 . Subsequently, this lack of effect on lipoprotein levels was also reported for GSK256073 37 . Thus, although this eliminated HCAR2/GPR109A as a drug target for the treatment of dyslipidemia, HCAR2 agonists do inhibit lipolysis, which potentially could be beneficial in e.g.…”
Section: Hcar2 As a Drug Target – From Dyslipidemia And Diabetes To I...mentioning
confidence: 72%
“… 43 Another GPR109A agonist that did not exert anti-dyslipidemia effect in clinical studies, GSK256073, should be assessed for antipsychotic activity as well. 67 …”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Based on the above, GPR109A agonists can be used for cancer prevention, 137 such as β-hydroxybutyrate and dietary fiber. Meanwhile, synthetic GPR109A-specific agonists MK1903, 141 acifran, 142 5-aminonicotinic acid (5-ANA), 143 GSK256073 (8-chloro-3-pentyl-1H-purine-2,6[3H,7H]-dione) 144 has been explored for its role in vascular and inflammatory diseases, but no preclinical and clinical studies have demonstrated their effectiveness in tumors. To find a strong targeting GPR109A agonist will provide a huge potential in tumor therapy.…”
Section: Metabolite Sensing and Epigenetic Regulation Of Fatty Acid M...mentioning
confidence: 99%